Bauhaus und Erwachsenenbildung Progressive Architektur im Verhältnis zu Reformpädagogik und Arbeiter:innen-Bewegung - Grotlüschen, Anke; Richter-Boisen, Anette (Verlag Barbara Budrich, 2023)
What role do the philosophy and pedagogical concepts of the Bauhaus play for adult education? And to what extent were progressive approaches to adult education able to influence Bauhaus architecture? The authors outline connections between the Bauhaus idea of form follows function and the history of institutionalised adult education, which reveal a surprising number of points of contact.